2003
DOI: 10.1111/1475-4762.00106
|View full text |Cite
|
Sign up to set email alerts
|

Relocating resource peripheries to the core of economic geography's theorizing: rationale and agenda

Abstract: Theorizing in economic geography has focused on core regions, industrial and non-industrial, old and new. Indeed, contemplation of the idea of globalization has reinforced this quest. This paper disputes this blinkered thinking that peripheralizes resource peripheries, and seeks to re-position and emphasize resource peripheries within economic geography's theoretical agenda, specifically that associated with the new 'institutional' approach. A truly 'global' economic geography cannot afford to ignore resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 31 publications
0
139
0
3
Order By: Relevance
“…One of the primary underpinnings of urban land teleconnections is that contemporary urbanization and globalization processes make the identification of distinct urban versus hinterland areas nearly impossible (31). The economic complexities and dynamic interrelations among local, regional, and global processes and commodity flows mean that there are important linkages between urban areas and nonurban places (32), which in turn have land use implications. Transboundary and nonlocal impacts on land from urbanization can occur in multiple and distant locations.…”
Section: Urban Land Teleconnectionsmentioning
confidence: 99%
“…One of the primary underpinnings of urban land teleconnections is that contemporary urbanization and globalization processes make the identification of distinct urban versus hinterland areas nearly impossible (31). The economic complexities and dynamic interrelations among local, regional, and global processes and commodity flows mean that there are important linkages between urban areas and nonurban places (32), which in turn have land use implications. Transboundary and nonlocal impacts on land from urbanization can occur in multiple and distant locations.…”
Section: Urban Land Teleconnectionsmentioning
confidence: 99%
“…The seasonal nature of the work, the shifting location of the worksites and a more ephemeral workforce comprised of post-secondary students, who usually only plant for a few seasons before exiting the industry, all contribute to this process. While mindful of Hayter et al (2003) caution against the uncritical application to resource peripheries of conceptual templates drawn from other contexts, we found that the concept of communities of practice, albeit in a modified form, provided useful insights into the development of work cultures amongst seasonal reforestation workers in northern Ontario.…”
Section: Resultsmentioning
confidence: 88%
“…The Canadian Geographer / Le Géographe canadien 52, no 2 (2008) 208 Brendan Sweeney and John Holmes Hayter et al (2003) argue that in debates about contemporary industrial restructuring and globalization, resource peripheries have not only tended to be treated as peripheral places but also peripheral to disciplinary theorizing in economic geography. They caution against the uncritical application to resource peripheries of conceptual templates based on the experience of industrial core regions.…”
Section: Conceptualmentioning
confidence: 99%
See 1 more Smart Citation
“…In many ways, Rossport could be used to illustrate all of these approaches. As a resource conflict, it provides an interesting illustration of critical resource geographies that centres such an analysis in the European Union, albeit at the western periphery of the EU (Hayter et al, 2003). It has been analysed as an environmental movement by a variety of sociologists, interested in understanding Rossport as yet another iteration of protests fuelled primarily by environmental concerns (Leonard, 2006).…”
Section: Putting Rossport To Work In Political Geographymentioning
confidence: 99%